PENERAPAN NILAI KARAKTER DISIPLIN PADA ANAK USIA DINI MELALUI KEGIATAN EKSTRAKURIKULER MEGAMBEL - Mardewi Widia Sari, Kadek; Nafisah, Aisyah Durrotun; Dwita Cahyani, Intan Regina (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2024)
Discipline is the key to making individuals adaptable to the rules that exist in society. There are various methods to develop discipline in early childhood. This research aims to explore how disciplinary characteristics are applied in megambel extracurricular activities. The research employs a descriptive qualitative approach through observation, interviews, and documentation for data collection. The study involved 15 group B students and several teachers as research subjects. The results reveal several implementations of discipline in megambel extracurricular activities, including: 1) megambel extracurricular trainers serve as role models by arriving early before the training schedule, and students are expected to arrive on time; 2) discipline in obeying rules, showed by teachers and students creating and agreeing on rules, with students understanding and adhering to them, such as sitting in the correct position for their musical instruments; 3) attitudinal discipline, illustrated by students not playing around during megambel extracurricular training sessions. The conclusion of the research is that megambel extracurricular activities train the character value of discipline in early childhood.